TroubleShot - Troubleshooting Hub - Haikal Iskandar; Rozlini Mohamed (Applied Information Technology And Computer Science, 2025)
The TroubleShot – Troubleshooting Hub project innovates the IT troubleshooting process of Regal Motor Holdings. Addressing the inefficiencies of the manual method utilized by the IT team, this project introduces a centralized digital solution. The aim is to streamline processes, enhance collaboration, and improve cost-effectiveness in IT operations. The manual method previously usually leads to delays, undocumented informations and costs the company more time and money. The proposed system resolves all this issue by streamlining the process of troubleshooting. Utilizing an object-oriented, web-based approach, the project employs the Prototyping Development Model for iterative development. Key features include a comprehensive Troubleshooting Library, advanced search, real-time tracking, performance evaluation, and detailed reporting. This digital hub significantly quickens issue resolution, fosters team collaboration, and optimizes resource use, marking a substantial improvement in IT troubleshooting efficiency.